2008
DOI: 10.1172/jci34088
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the nervous system–specific HSN2 exon of WNK1 cause hereditary sensory neuropathy type II

Abstract: Hereditary sensory and autonomic neuropathy type II (HSANII) is an early-onset autosomal recessive disorder characterized by loss of perception to pain, touch, and heat due to a loss of peripheral sensory nerves. Mutations in hereditary sensory neuropathy type II (HSN2), a single-exon ORF originally identified in affected families in Quebec and Newfoundland, Canada, were found to cause HSANII. We report here that HSN2 is a nervous system-specific exon of the with-no-lysine(K)-1 (WNK1) gene. WNK1 mutations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 46 publications
4
141
0
Order By: Relevance
“…92 Similarly, mutations in WNK1 could also alter NGF/TrkA signaling through its protein kinase activity, although abnormalities in kinase activity for particular substrates have not been examined in detail in mutant proteins that contain the pathogenic exon 8B. 93 Nevertheless, WNK1 activates Erk5, 94 and Erk5 is a critical mitogen-activated protein kinase required for retrograde NGF/TrkA survival signaling in NGF-dependent neurons. 95 Alterations in WNK1-mediated activation of Erk5 could lead to altered sensory and sympathetic neuron survival in HSAN2 caused by WNK1 mutations.…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…92 Similarly, mutations in WNK1 could also alter NGF/TrkA signaling through its protein kinase activity, although abnormalities in kinase activity for particular substrates have not been examined in detail in mutant proteins that contain the pathogenic exon 8B. 93 Nevertheless, WNK1 activates Erk5, 94 and Erk5 is a critical mitogen-activated protein kinase required for retrograde NGF/TrkA survival signaling in NGF-dependent neurons. 95 Alterations in WNK1-mediated activation of Erk5 could lead to altered sensory and sympathetic neuron survival in HSAN2 caused by WNK1 mutations.…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…An interesting recent study has reported that neuronal tissues express two distinct splice variants of WNK1, which possess an inserted sequence within the C-terminal non-catalytic domain that is expressed from distinct exons (termed exon 8b and exon HSN2) ( Fig. 1) (Shekarabi et al, 2008). Most importantly, this study reported that, human mutations that lie within exon HSN2 as well as in exon 6 of WNK1 resulted in an early-onset autosomal-recessive loss-of-pain-perception disorder termed hereditary sensory and autonomic neuropathy type II (HSANII) (Shekarabi et al, 2008).…”
Section: Key Features Of Wnk Isoformsmentioning
confidence: 99%
“…1) (Shekarabi et al, 2008). Most importantly, this study reported that, human mutations that lie within exon HSN2 as well as in exon 6 of WNK1 resulted in an early-onset autosomal-recessive loss-of-pain-perception disorder termed hereditary sensory and autonomic neuropathy type II (HSANII) (Shekarabi et al, 2008). The described mutations result in the truncation of a large region of the non-catalytic C-terminal domain of the WNK1 protein; this does not affect the kinase domain (Shekarabi et al, 2008).…”
Section: Key Features Of Wnk Isoformsmentioning
confidence: 99%
“…All immunohistochemistry and tissue preparations were performed as described previously (Howard et al, 2002;Shekarabi et al, 2008). A mix of anti-axonal markers SMI31 and SMI32 (Covance, each at 1:500), anti-glutamic acid decarboxylase (GAD67; Novus Biologicals, 1:200) followed by donkey antimouse Alexa Fluor 488 or anti-rabbit Alexa Fluor 488 (Molecular Probes, all at 1:1000) were used to label axons , and GABAergic neurons and synaptic terminals, respectively.…”
Section: ⌬18/⌬18mentioning
confidence: 99%